2011
DOI: 10.1371/journal.pgen.1002239
|View full text |Cite
|
Sign up to set email alerts
|

Celsr3 Is Required for Normal Development of GABA Circuits in the Inner Retina

Abstract: The identity of the specific molecules required for the process of retinal circuitry formation is largely unknown. Here we report a newly identified zebrafish mutant in which the absence of the atypical cadherin, Celsr3, leads to a specific defect in the development of GABAergic signaling in the inner retina. This mutant lacks an optokinetic response (OKR), the ability to visually track rotating illuminated stripes, and develops a super-normal b-wave in the electroretinogram (ERG). We find that celsr3 mRNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 54 publications
4
36
1
Order By: Relevance
“…Previous studies deleted the Celsr3 gene either from early embryonic development or early embryonic brain development (8)(9)(10). When Celsr3 was deleted from the embryonic forebrain using Emx1-Cre, a number of defects were found in neuronal cell numbers, migration, and axon guidance.…”
Section: Discussion Opposing Roles Of Celsr3 and Vangl2 In Glutamatermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies deleted the Celsr3 gene either from early embryonic development or early embryonic brain development (8)(9)(10). When Celsr3 was deleted from the embryonic forebrain using Emx1-Cre, a number of defects were found in neuronal cell numbers, migration, and axon guidance.…”
Section: Discussion Opposing Roles Of Celsr3 and Vangl2 In Glutamatermentioning
confidence: 99%
“…Recent studies suggest that mutations of some components of the PCP signaling pathway, Celsr3/Fmi and Vangl2, affect GABAergic circuit development in zebrafish retina, GABAergic motoneuron synapse development in Caenorhabditis elegans, and hippocampal/cortical glutamatergic and GABAergic synapse formation (5)(6)(7)(8)(9)(10)(11). PCP components are critical regulators of neuronal migration and axon guidance, which take place before synapse formation and their mutations may secondarily affect synapse formation (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19). Therefore, evaluating the specific functions of PCP components in synapse formation requires conditionally knocking out these components in defined synapses after the development of axons and dendrites.…”
mentioning
confidence: 99%
“…The mammalian Celsr genes are the so-called core PCP genes that have conserved as well as newly diversified functions. In particular, the vertebrate Celsr3 gene has been shown to regulate axonal projections, dendrite development, neuronal migration, ciliogenesis, and retina circuit development (8)(9)(10)(11)(12)(13)(14)(15)(16). However, very little is known about Celsr gene regulation.…”
mentioning
confidence: 99%
“…The authors concluded that picrotoxininduced reduction in the b-wave results from inactivation of the GABA C receptors of ON bipolar cells. However, many other data including those obtained in our laboratory indicate that the blockade of ionotropic GABA receptors by picrotoxin leads to an increase of the b-wave amplitude (frog: Arnarsson & Eysteinsson, 1997;Belcheva & Kupenova, 1980;Belcheva & Vitanova, 1974;Bonaventure, Wioland, & Jardon, 1986;DeVries & Friedman, 1978;Katz et al, 1991;Kupenova, Popova, & Vitanova, 2008;Popova, 1989Popova, , 2000Popova et al, 1986;turtle: Belcheva & Vitanova, 1978;Kupenova et al, 1991Kupenova et al, , 1997Vitanova et al, 1997;fish: Chappell & Rosenstein, 1996;Lewis et al, 2011). The effect is evident in conditions of both dark and light adaptation, indicating that it does not depend on the type of the photoreceptor input.…”
Section: Introductionmentioning
confidence: 81%
“…The effects of picrotoxin on the d-wave resembled that on the b-wave. Although Bonaventure, Wioland, and Jardon (1986) did not find any effect of picrotoxin on the d-wave, other authors reported that picrotoxin enhances the amplitude and delays the time course of the d-wave (Arnarsson & Eysteinsson, 1997;Belcheva & Kupenova, 1980;Belcheva & Vitanova, 1974Kupenova et al, 1991Kupenova et al, , 1997Lewis et al, 2011;Popova, 1989Popova, , 2000Popova et al, 1986;Vitanova et al, 1997;Xu & Karwoski, 1995). Picrotoxin revealed a prominent OFF component in all rod retina of skate (Chappell & Rosenstein, 1996) and in dark adapted toad retina (Katz et al, 1991).…”
Section: Introductionmentioning
confidence: 95%